2011
DOI: 10.1111/j.1365-2559.2011.03747.x
|View full text |Cite
|
Sign up to set email alerts
|

Sox10‐positive sustentacular cells in neuroendocrine carcinoma of the lung

Abstract: Sox10-positive sustentacular cells were observed in carcinoid tumours but not in high-grade NECs. Sustentacular-rich carcinoid tumours did not show a correlation with the occurrence of lymph node metastasis or survival. The sustentacular cells found differed in morphological subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Most of the vimentin‐positive cells in our study were considered to be sustentacular cells, because the positive cells had a stellate shape and several authors have reported that 18–82% of pulmonary carcinoid tumours contain sustentacular cells 35,36 . We have found recently that the presence of sustentacular cells differs in the morphological subtypes of carcinoid tumour, with spindle‐cell types being the most prevalent subtype 37 . This immunostaining pattern of SCCTs with regard to intratumoural sustentacular cells might result in a misdiagnosis of mesenchymal tumour.…”
Section: Discussionmentioning
confidence: 58%
“…Most of the vimentin‐positive cells in our study were considered to be sustentacular cells, because the positive cells had a stellate shape and several authors have reported that 18–82% of pulmonary carcinoid tumours contain sustentacular cells 35,36 . We have found recently that the presence of sustentacular cells differs in the morphological subtypes of carcinoid tumour, with spindle‐cell types being the most prevalent subtype 37 . This immunostaining pattern of SCCTs with regard to intratumoural sustentacular cells might result in a misdiagnosis of mesenchymal tumour.…”
Section: Discussionmentioning
confidence: 58%
“…This scenario is particularly well illustrated in paragangliomas arising in unusual organs such as thyroid, lung, and pancreas where the diagnosis of medullary carcinoma, carcinoid tumor, or islet cell tumor might be considered. Sustentacular cells characteristic of paraganglioma can be seen in carcinoid tumors and neuroendocrine carcinomas of a variety of organs, [22][23][24] and the Zellballen pattern can be seen as well. 25 In addition, a subset of paragangliomas show cytokeratin expression, which might further support the diagnosis of carcinoid tumors, 26 or, alternatively, the possibility of carcinoma might be raised.…”
Section: Discussionmentioning
confidence: 99%
“…They regulate various developmental processes, and their encoded proteins are involved in different tumors as tumor promoter or suppressor. Sox10 is overexpressed in peripheral neural and melanocytic tumors [11] and in solid tumors such as neuroendocrine tumor of the lung [13], basal-like, triple-negative and metaplastic carcinoma of breast [14], and hepatocellular carcinoma [17]. Sox10 knockdown in human melanoma cells induces senescence and suppresses melanomagenesis [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sox10 has also been found in some human solid tumors. For example, in neuroendocrine tumors of the lung, it is expressed by sustentacular cells, the presence of which is inversely correlated with neuroendocrine tumor grade [13]. Sox10 expression has been reported in basal-like, triple-negative and metaplastic carcinoma of breast [14], acinic cell carcinoma, adenoid cystic carcinoma, myoepithelial carcinoma, pleomorphic adenoma of salivary gland [15,16], and hepatocellular carcinoma [17].…”
Section: Introductionmentioning
confidence: 97%